Notes on the typification of the name Curtia montevidensis (Gentianaceae) - Deng, Yunfei (Phytotaxa, 2023)
The genus Curtia Chamisso & Schlechtendal (1826: 209, t. 4) is a small genus of the family Gentianaceae. It comprises eight species distributed in Mexico, tropical regions of Central and South America (Crespo & Marcondes-Ferreira 2009, Struwe & Pringle, 2018).